Vietnam in the democratization process: Dynamics from the process of international integration and the development of information-communication technology - Thoa, Tu Thi (Faculty of Social and Political Science, Universitas Airlangga, 2024)
This article delves into the complex dynamics of Vietnam’s democratization process, highlighting the simultaneous influences of international integration and advancements in science and technology. This study investigates the impact of Vietnam’s increasing involvement in the global economy and international community, as well as its adoption of technological advancements, on the country’s path toward democratization. The study utilizes a mixed approach, blending qualitative analysis of scientific documents, Vietnamese government policies, and quantitative data on the democracy index from international organizations. It identifies international integration as a doubleedged sword: on one hand, it boosts economic growth and development, driving the democratic transition process forward; on the other hand, it also leads to economic dependence and inequality, potentially impeding democratic reform. The findings of this study show that the rapid progress of science and technology, especially information and communication technology, presents both opportunities and difficulties for Vietnam’s democratic process. It provides unparalleled opportunities for widespread involvement in political activities and the spread of democratic principles, but it also carries the risk of social unrest and the potential for the authoritarian state to control and manipulate information.